Purwarupa Alat Bantu Penuang Gelas Ukur 100 ml Menggunakan Motor Servo Berbasis Mikrokontroler - Azis Muslim; Regita Robi'ah; Herfin Yienda Prihensa (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Pouring liquid from a measuring cylinder requires careful consideration of the appropriate tilt angle to achieve optimal emptying conditions. Drip time and emptying time are critical parameters for maximizing pouring efficiency. This study presents the design of a microcontroller-based system to automate the pouring process of a measuring cylinder. The developed prototype utilizes an MG996R servo motor as the actuator and an Arduino Uno microcontroller as the control unit. The system comprises two main components: a servo motor-based mechanical pouring structure and microcontroller-based automation software. The initial phase involved designing the structure using 3D modelling software, manufacturing, and manual assembly. Simulations were conducted using SolidWorks software. Experimental results showed that the liquid pouring time at a 120° angle was 9.89 seconds with a 4.76% error, at 150° was 12.38 seconds with a 3.78% error, and at 170° was 13.97 seconds with a 2.73% error. The total emptying time for a 100 ml measuring cylinder was recorded at 62.69 seconds with a 0.81% error.